The ROOT HAIRLESS 1 gene encodes a nuclear protein required for root hair initiation in Arabidopsis. - Schneider, K; Mathur, J; Boudonck, K; Wells, B; Dolan, L; Roberts, K (1998)
The epidermis of Arabidopsis wild-type primary roots, in which some cells grow hairs and others remain hairless in a position-dependent manner, has become an established model system to study cell differentiation. Here we present a molecular analysis of the RHL1 (ROOT HAIRLESS 1) gene that, if mutated, prevents the formation of hairs on primary roots and causes a seedling lethal phenotype. We have cloned the RHL1 gene by use of a T-DNA-tagged mutant and found that it encodes a protein that appears to be plant specific. The predicted RHL1 gene product is a small hydrophilic protein (38.9 kD) containing putative nuclear localization signals and shows no significant homology to any known amino acid sequence. We demonstrate that a 78-amino-acid sequence at its amino terminus is capable of directing an RHL1-GFP fusion protein to the nucleus. The RHL1 transcript is present throughout the wild-type plant and in suspension culture cells, but in very low amounts, suggesting a regulatory function for the RHL1 protein. Structural evidence suggests a role for the RHL1 gene product in the nucleolus. We have examined the genetic relationship between RHL1 and GL2, an inhibitor of root hair initiation in non-hair cells. Our molecular and genetic data with double mutants, together with the expression analysis of a GL2 promoter-GUS reporter gene construct, indicate that the RHL1 gene acts independently of GL2.